FINDRISC modified for Cuba as a tool for the detection of prediabetes and undiagnosed diabetes in cuban population - Cabrera-Rode, Eduardo; Díaz-Díaz, Oscar; Orlandi González, Neraldo; Ronald, Mohan (Revista peruana de medicina experimental y salud pública, 2025)
Motivation for the study. There is an increase in obesity and diabetes mellitus cases in Cuba, so it is necessary to provide easy to use, fast and inexpensive tools for the identification of people with dysglycemia. Main findings. For the first time in CUBA, the optimal cut-off point for FINDRISC, LA-FINDRISC and modified FINDRISC for Cuba (CUBDRISC) questionnaires was established with its own anthropometric parameters to identify people with dysglycemia. Implications. The use of the CUBDRISC scale as a simple, fast and low-cost tool for the active screening of people with dysglycemia in Cuban population will be useful to establish timely intervention strategies for people with risk score to develop dysglycemia. To evaluate the Finnish Diabetes Risk Score (FINDRISC) modified for Cuba as a tool for the detection of prediabetes and undiagnosed diabetes in Cuban population. An analytical cross-sectional and secondary source epidemiological study was conducted in 3737 adults aged 19 years and older with at least one risk factor for diabetes, they did not have previous diagnosis of prediabetes and diabetes mellitus and underwent oral glucose tolerance test for the diagnosis of dysglycemia. We applied the FINDRISC and the FINDRISC modified for Latin America (LA-FINDRISC) and Cuba (CUBDRISC), each with their own anthropometric parameters. The ROC curve was used to establish the cut-off point of each scale for the diagnosis of dysglycemia. Sensitivity, specificity, predictive values and likelihood ratios were calculated. The concordance between scales was calculated with Cohen's Kappa coefficient. We found that 34.5% (n=1289) of the subjects were diagnosed with dysglycemia (28.1% had prediabetes and 6.4% had type 2 diabetes without previous diagnosis). The LA-FINDRISC and CUBDRISC scales showed an almost perfect concordance with the FINDRISC scale for the different cut-off values from 11 to 16 (0.882-0.890 and 0.910-0.922, respectively). The optimal cutoff point for detecting persons with dysglycemia was ≥ 13 for the FINDRISC and CUBDRISC scales (sensitivity was 63.6% and 61.6%; specificity was 84.3% and 86.0%, respectively) and ≥11 for LA-FINDRISC (sensitivity 58.0% and specificity 88.0%). We found almost perfect concordance between the diabetes risk scales. The FINDRISC score modified for Cuba proved to be a useful tool to identify persons with prediabetes and diabetes with a cut-off point of 13 in a Cuban population.